Author Correction: Incorporation of Ursolic Acid in Liquid Crystalline Systems Improves the Antifungal Activity Against Candida sp. (Journal of Pharmaceutical Innovation, (2020), 10.1007/s12247-020-09470-0) - Marena, Gabriel Davi [UNESP]; Fonseca-Santos, Bruno [UNESP]; dos Santos Ramos, Matheus Aparecido [UNESP]; dos Santos, Karen Cristina [UNESP]; Bauab, Taís Maria [UNESP]; Chorilli, Marlus [UNESP] (Springer Nature, 2020)
The original version of this article unfortunately contained a mistake. The name of the 3rd author was incorrectly presented. The correct name of the 3rd author is “Matheus Aparecido dos Santos Ramos.”.